Pengaruh Variasi Aktivator ZnCl2 dan NaOH terhadap Efisiensi Adsorpsi Karbon Aktif dari Kayu Cempedak (Artocarpus Champeden) sebagai Adsorben dalam Limbah Sasirangan - Lutfiana Marisa; Mukarramah, Anisah; Fatya, Alvian Ikhsanul (Al Kawnu : Science and Local Wisdom Journal, 2024)
Sasirangan is a batik originating from South Kalimantan. The batik industry produces cloudy and concentrated liquid waste, so efforts are needed to reduce the negative impacts. The manufacture of cempedak wood activated carbon has been carried out. This research aims to determine the adsorption efficiency of cempedak wood active carbon on sasirangan waste using the UV-Vis test. Cempedak wood activated carbon is made using a carbonation and activation process. The activators used in the research are basic and neutral compounds, namely NaOH and ZnCl2. The research results showed that cempedak wood activated carbon with ZnCl2 activator showed a higher adsorption efficiency value of 31% compared to the NaOH activator whose adsorption efficiency value was 2%. Based on the observation results, it can be concluded that cempedak wood activated carbon with ZnCl2 activator is more effective than NaOH activator.